2012
DOI: 10.3109/1061186x.2012.662686
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of microparticles containing plasmid DNA encoding hepatitis-B surface antigen

Abstract: The role of albumin-based chitosan microparticles on enhancing immune response of plasmid DNA (pDNA) to hepatitis-B surface antigen (HBsAg) vaccine after oral administration was investigated in mice. The pDNA encoding HBsAg was entrapped in albumin microparticles using a one-step spray drying technique optimized in our laboratory. The encapsulated particles were also characterized in vitro for their shape, size, encapsulation efficiency, content, and stability. Albumin microparticles could protect the DNA from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Although many efforts have been put into the design and modification of chitosan nanoparticles, a viable oral delivery system for DNA vaccines is still lacking [33]. One major obstacle to achieving satisfactory oral vaccinations in the DNA degradation results when exposed to the acidic gastric environment and the subsequent decreased uptake via lymphoid tissue in the gastrointestinal tract [35,36,37]. We demonstrated here, that compared with plain chitosan nanoparticles, A.C.NPs protect DNA against degradation in stimulated gastric fluid (pH 1.5).…”
Section: Discussionmentioning
confidence: 99%
“…Although many efforts have been put into the design and modification of chitosan nanoparticles, a viable oral delivery system for DNA vaccines is still lacking [33]. One major obstacle to achieving satisfactory oral vaccinations in the DNA degradation results when exposed to the acidic gastric environment and the subsequent decreased uptake via lymphoid tissue in the gastrointestinal tract [35,36,37]. We demonstrated here, that compared with plain chitosan nanoparticles, A.C.NPs protect DNA against degradation in stimulated gastric fluid (pH 1.5).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the particles loaded with drugs obtained by spray-drying could be administered by different routes such as oral [127][128][129][130][131][132], pulmonary [12,23,82,133,134), ophthalmic [93,111,135], parenteral [22,38,136], nasal [60,120,121,137], and vaginal [138], stressing its great In vitro tests showed that their mucoadhesion was 2-fold higher than that of a hydroxyethylcellulose gel formulation [138].…”
Section: Different Routes Of Administration Of Drug-loaded Polymeric mentioning
confidence: 99%
“…The vaccine formulation was prepared by spray drying technique [810,1824]. Briefly, HPMCAS and Eudragit® FS 30D were dissolved in an alkaline solution, followed by addition of chitosan glycol.…”
Section: Methodsmentioning
confidence: 99%